Management Of Fractures In Myasthenia Gravis - MAZHERUDDIN ALI KHAN; V.R. SUJIT KUMAR (International Journal of Pharma and Bio Sciences, 2012)
Management of a fracture in a patient having myasthenia gravis disease is very complicated. Myasthenia gravis is an autoimmune disorder characterized by muscle weakness. The disease tends to strike women more often than men, usually affecting women between the ages of 20 and 40 . After about age 50, both sexes tend to be equally affected . The prevalence of MG is approximately 100 per 100000 population with incidence of 2-4 per 100 000 per annum .here in we report a case of fracture neck of femur with 25 yrs h/o MG on Rx, which were managed with perioperative precautions in anesthethic and orthopaedics point of view by hemiarthroplasty with bipolar prosthesis.